Collagen fibrils and cell nuclei are entrapped within Randall's plaques but not in CaOx matrix overgrowth: A microscopic inquiry into Randall's plaque stone pathogenesis. Issue 7 (30th November 2021) - Canela, Victor Hugo; Bledsoe, Sharon B.; Worcester, Elaine M.; Lingeman, James E.; El‐Achkar, Tarek M.; Williams, James C.
Abstract: Calcium oxalate (CaOx) stones can grow attached to the renal papillary calcification known as Randall's plaque. Although stone growth on Randall's plaque is a common phenomenon, this mechanism of stone formation is still poorly understood. The objective of this study was to investigate the microenvironment of mature Randall's plaque, explore its molecular composition and differentiate plaque from CaOx overgrowth using multimodal imaging on demineralized stone sections. Fluorescence imaging showed consistent differences in autofluorescence patterns between Randall's plaque and calcium oxalate overgrowth regions. Second harmonic generation imaging established the presence of collagen only in regions of decalcified Randall's plaque but not in regions of CaOx overgrowth matrix. Surprisingly, in these stone sections we observed cell nuclei with preserved morphology within regions of mature Randall's plaque. These conserved cells had variable expression of vimentin and CD45. The presence of nuclei in mature plaque indicates that mineralization is not necessarily associated with cell death. The markers identified suggest that some of the entrapped cells may be undergoing dedifferentiation or could emanate from a mesenchymal or immune origin. We propose that entrapped cells may play an important role in the growth and maintenance of Randall's plaque. Further characterization of these cells and thorough analyses of the mineralized stone forming renal papilla will be fundamental in understanding the pathogenesis of Randall's plaque and CaOx stone formation.